1991
DOI: 10.1680/geot.1991.41.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Subsidence effects on clay barriers

Abstract: Centrifuge model tests have been performed to study the response of clay barriers subjected to differential deformations. The modes of deformation that have been observed are relevant to those that might occur as the result of differential settlements of waste material leading to deformation of cover liners, or from non-uniform soil strength profiles or the propagation of deep-sited subsidence towards the surface, leading to deformations of the base liner. Plane model liners were constructed both from pure kao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 0 publications
1
15
0
1
Order By: Relevance
“…Researchers in the past have used consolidated clay to model the compacted clay liners (Jessberger and Stone, 1991) and processed MSW to model the waste (Syllwasschy et al, 1996). The scaling laws of centrifuge modelling are given by Schofield (1980) and Taylor (1995).…”
Section: Centrifuge Modelling Of Landfill Componentsmentioning
confidence: 99%
“…Researchers in the past have used consolidated clay to model the compacted clay liners (Jessberger and Stone, 1991) and processed MSW to model the waste (Syllwasschy et al, 1996). The scaling laws of centrifuge modelling are given by Schofield (1980) and Taylor (1995).…”
Section: Centrifuge Modelling Of Landfill Componentsmentioning
confidence: 99%
“…The rapid, preferential transmission of water through the full depth of a crack (which can be on the order of metres) is potentially a significant mechanism for strength reduction in earthworks that could lead to earth structure failure. Tensile failure is also reported in clay barriers, where differential settlement of waste material causes cracking and a reduction in liner performance as an effective hydraulic barrier (Jessberger and Stone, 1991). Chemically modified/cement stabilised materials in road and rail line sub bases can also undergo tensile cracking induced by traffic generated cyclic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…The impervious barriers of landfill covers are more likely to be subjected to more mechanical damage compared to bottom lining systems since the former is subjected to lower overburden pressure. Excessive differential settlements can cause development of tension cracks in the clay barrier resulting in loss of integrity of whole cover system (Jessberger and Stone, 1991;Keck and Seitz, 2002;Dickinson and Brachman, 2006;Sharma and De, 2007;Heerten and Koerner, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that clay barriers lose the integrity at the onset of differential settlement (Jessberger and Stone, 1991;Scherbeck and Jessberger, 1993;LaGatta et al, 1997;Edelmann et al, 1999;Viswanadham and Mahesh, 2002;Rajesh and Viswanadham, 2011). But the studies pertaining to the deformation behaviour of composite barriers with a geomembrane overlying the compacted clay barrier subjected to differential settlements in a centrifuge is not yet reported to the best of authors' knowledge.…”
Section: Introductionmentioning
confidence: 99%